TEACHING READING IN A FOREIGN LANGUAGE IN ESP - Yaxshiboyev, G.O. (SCIENCE and SOCIETY, 2021)
In this article we observed role of reading, types and easy analyzing of the given unknown texts. Reading plays one of the most important roles in the process of learning a foreign language. To be able to read means, first of all, to be able to guess by letter about the words that are designated by them.